LARVICIDAL POTENCY OF Andrographis paniculata PLANT EXTRACT ON Anopheles gambiae LARVAE - C. U. Uzochukwu; U. A. Offor; I. E. Obiefule; E. O. Ogbuefi; C. A. Imakwu (The Bioscientist)
Control of mosquito vectors has relied heavily on chemicals which has disadvantages such as resistance development, and environmental hazards. This study investigated the phytochemical constituents and larvicidal potency of Andrographis paniculata against Anopheles gambiae larvae. Soxhlet and Maceration techniques were utilized, with ethanol and water as solvents respectively. Ten fourth instar larvae of An. gambiae were exposed to three replicates of different concentrations (20%, 15%, 10%, and 5%) of the extracts, using a Completely Randomised Design with ethanol and water in soxhlet and maceration extraction respectively. Monitoring was conducted at intervals of 0, 1, 3, 24, and 48-hours post-treatment. The data gathered were examined through log-probit regression and analysis of variance. Findings indicated increased mortality with higher levels of concentration and exposure time to Soxhlet extract, displaying a statistically significant difference (p = 0.035) (p < 0.05). Result showed A. paniculata had larvicidal effect on An. gambiae larvae. There was concentration dependent mortality as mortality increases with increase in concentration of both extracts. For Soxhlet extract, the highest concentration of 20% caused 86.7% mortality while the lowest concentration of 5% caused 49.0% mortality. Similarly, for maceration extract, 20% concentration caused 76.7% mortality while 5% caused 40.0% mortality. The lethal concentration LC50 and LC90 were 6.9% and 36.58% respectively for soxhlet extract while they were 9.1% and 56.1% respectively for maceration extract. Also, the LT50 and LT90 for Soxhlet extract was lower (23hrs and 53hrs) than the maceration extract (48.7hrs and 60hrs). Result also showed that Soxhlet extraction produced more bioactive compounds than the maceration. This study showed that A. paniculata is a potential larvicidal agents in the control of Anopheles gambiae. These findings suggest that A. paniculata could serve as an eco-friendly alternative for controlling malaria vectors.